Beyond the Classroom Screen: Student Preferences for Blended Erudition in Open and Distance Learning Institutions - Onikoyi Olawale Abayomi; Onikoyi Yetunde Raliat Adeola; Bankole Olabisi Latifat; Nafiu Aminat Adejoke (Managere: Indonesian Journal of Educational Management, 2026)
Open and distance learning (ODL) institutions in Nigeria face persistent challenges in delivering digital instruction to geographically dispersed students due to weak infrastructure, high internet costs, and limited institutional support. This study examined undergraduate adoption and preference for online and blended learning in selected ODL institutions in Lagos State and identified technological factors influencing adoption. A descriptive survey design was used with 480 purposively selected undergraduates from three institutions. Data were collected using structured questionnaires and analyzed using mean scores, z-scores, and chi-square tests. Findings indicate a statistically significant preference for blended learning over fully online delivery. Key barriers include high data costs, unstable electricity supply, inadequate technical support, and low digital literacy, although students still recognize the efficiency and flexibility of online learning. The study concludes that limited adoption is driven more by structural readiness constraints than learner resistance. The findings imply that institutional and policy interventions should prioritize investment in digital infrastructure, affordable internet access, reliable power systems, continuous technical support, and sustained digital literacy training to ensure equitable and effective ODL delivery.